The Effect of Transition Metals on Quasicrystalline Phase Formation in Mechanically Alloyed Al65Cu20Fe15 Powder - M. Mitka; D. Kalita; Anna Góral; L. Lityńska-Dobrzyńska (Archives of Metallurgy and Materials, 2020)
The effect of replacing iron with transition metals (M = Mn, Cr, Co) on the microstructure of mechanically alloyed Al65Cu20Fe15 quasicrystalline powder was examined by X-ray diffraction and transmission electron microscopy methods. Powders of various compositions were milled in a high-energy planetary ball mill up to 30 hours at a rotation speed 350 rpm using WC milling media. The amount of the fourth additions was constant in all powders and Fe atoms were replaced with Mn, Cr or Co in a 1:1 ratio, while the content of the Al and Cu was selected in two ways: they remained the same as in the initial ternary Al65Cu20Fe15 alloy or changed to obtain e/a ratio = 1.75 (optimal for icosahedral quasicrystalline phase). Quasicrystalline phase formed in the quaternary Al65Cu20Fe7.5M7.5 powders, whereas in the second group of compositions only crystalline phases were identified.